Plan estratégico para la dirección distrital 05d04 Pujilí - Saquisilí salud en el periodo 2015-2016 - Cajas Acurio, Germania Maricela (2016)
The present research had as goal to improve the strategic direction of the Direction Distrital 05D04 Pujili - Saquisili Health, allowing the timely provision of all units; the research was made through an analysis of internal and external factors (S.W.O.T.), using techniques applied to workers at the district 05D04 Pujili - Saquisili, such as survey, interview and observation, also by the use of a methodology of non-experimental design and descriptive kind, the inductive method were used. The applied in the research helped to know that the main causes of the inefficient strategic direction are the frequent rotation of staff in the different hierarchical levels, lack of liquidity for the mismanagement by the authorities in the country….